2013
DOI: 10.5152/etd.2013.39
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Cerebral Surface Area of the Newborn Brain Using Stereological Methods

Abstract: Giriş İnsan beyni yaklaşık 1400 gr kadar olup, tüm vücut ağırlığının %2'si kadardır. Yenidoğanda bu oran %10'a kadar çıkmaktadır (1, 2). Yenidoğan beyni erişkin beyninin 1/3-1/4'ü kadardır (3). İnsanda beyin gelişim süreci embriyonal dönemde başlar ve yaklaşık 15 yıl boyunca sürer. Büyüme oranı intrauterin yaşamda ve ilk postnatal aylarda oldukça hızlıdır (4). Son yirmi yılda yapılan çalışmalarda genç erişkin beyninin toplam hacminin yaklaşık olarak %90 kadarının 5 yaşına kadar kazanıldığı belirtilmiştir. Tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
2
0
1
Order By: Relevance
“…The various anatomic and physiological changes beginning with the birth of an organism and continuing with aging throughout the life span have attracted the attention of many researchers [9]. The volumes of the brain and its sections in healthy individuals are important in the evaluation of both the clinical pathological condition and the normal aging process [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The various anatomic and physiological changes beginning with the birth of an organism and continuing with aging throughout the life span have attracted the attention of many researchers [9]. The volumes of the brain and its sections in healthy individuals are important in the evaluation of both the clinical pathological condition and the normal aging process [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been demonstrated that there is a volumetric decrease in brain tissue and cerebellar atrophy occurs with aging [11,12]. Calculation of the cerebellum volume is important to accurately assess size differences that may later occur and calculate the changes [9].…”
Section: Discussionmentioning
confidence: 99%
“…BT' de aksiyel imajlar 5 mm kesit kalınlığı ile elde olundu. Lezyonların boyutları tespit edilip, lezyon hacimleri stereolojik yöntemlerle hesaplandı (20). Lezyonların BT dansiteleri Haunsfield unitesi (HU) cinsinden ölçüldü.…”
unclassified